Perkembangan Islam di Arab Saudi (Studi Sejarah Islam Modern) - Abu Haif (Universitas Islam Negeri Alauddin Makassar, 2015)
The purpose of this writing is trying to describe the development of Islam in Saudi Arabia as a historical study. As far as we know, Saudi Arabia is a monarchi constitutional state which locates on Arab Peninsula. Saudi Arabia was existed on 23th September 1932. Further, Saudi Arab had massive developments by their six kings before. Right now, under the conductiveness of King Salman as a seventh king, Saudi Arabia has been located as a great state among the superior state in this world. It is caused by the leadership form of Salman, like becomes a moderat leader and takes diplomatic approach to solve social, religion, economy and political issues in his country. As consequences of those policies, the development of Islam will appear on Saudi Arabia Kingdom.